PATIENT SATISFACTION ON NATIONAL HEALTH INSURANCE (JKN) SERVICES - Lestariningrum, Siti; Bachtiar, Adang (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The National Health Insurance (JKN) is an insurance system that guarantee all of Indonesian people can access the health services. By registered as a JKN member, people can access and get treatment in health facilities that collaborate with JKN. Measuring the quality of JKN services can be done by measure the patient?s satisfaction on JKN. This study aims to determine the factor of patient?s satisfaction with JKN services. Methods: This study was a systematic review used PRISMA guidelines. Data obtained from electronic database of Google Scholar that published in 2019 and used Indonesia language. The keywords that been used was satisfaction with JKN services to find the relevant articles. Results: The search found 968 articles from Google Scholar database. Articles that did not fulfil the inclusion criteria must be excluded. Totally, 7 articles that contained patient satisfaction with JKN services in hospital had been chosen to analyzed in this study. These articles showed that patient satisfaction with JKN services influenced by some factors such as tangible, reliability, responsiveness, assurance, and empathy. Conclusion: Factors influenced the patient?s satisfaction with JKN services in hospital were tangible, reliability, responsiveness, assurance, and empathy. These factors influenced by the quality of the hospital services. To increase the patient?s satisfaction, hospital must improve and develop facilities and quality of the hospital services.